6-Phenoxy-2-phenylbenzoxazoles, novel inhibitors of receptor for advanced glycation end products (RAGE). Issue 15 (1st August 2015) - Choi, Kwanghyun; Lim, Kwang Su; Shin, Juhee; Kim, Seo Hee; Suh, Young-Ger; Hong, Hyun-Seok; Kim, Hee; Ha, Hee-Jin; Kim, Young-Ho; Lee, Jiyoun; Lee, Jeewoo
Graphical abstract: Abstract: Receptor for advanced glycation end products (RAGE) is known to be involved in the transportation of amyloid β (Aβ) peptides and causes the accumulation of Aβ in the brain. Moreover, recent studies suggest that the interactions between RAGE and Aβ peptides may be the culprit behind Alzheimer's disease (AD). Inhibitors of the RAGE–Aβ interactions would not only prevent the accumulation of toxic Aβ in the brain, and but also block the progress of AD, therefore, have the potential to provide a 'disease-modifying therapy'. In this study, we have developed a series of 6-phenoxy-2-phenylbenzoxazole analogs as novel inhibitors of RAGE. Among these derivatives, we found several effective inhibitors that block the RAGE–Aβ interactions without causing significant cellular toxicity. Further testing showed that compound 48 suppressed Aβ induced toxicity in mouse hippocampal neuronal cells and reduced Aβ levels in the brains of a transgenic mouse model of AD after oral administration.